The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.juro.2012.10.065
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Risk Stratification of Patients with Urothelial Carcinoma of the Bladder with Recurrence After Radical Cystectomy

Abstract: Our data confirm that recurrent urothelial carcinoma after radical cystectomy is a highly aggressive, lethal disease. Seven clinicopathological factors were identified that predicted post-recurrence overall survival. Our risk model based on the 4 variables could be useful to provide relevant prognostic information to patients and physicians, and better stratify patients in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 19 publications
3
39
1
1
Order By: Relevance
“…In addition to serum ALP reported by von der Maase et al (5), the recent report by Nakagawa et al (11) demonstrated that serum CRP and serum lactate dehydrogenase (LDH) levels were independent predictors of poorer survival, analyzing 114 patients who were treated with radical cystectomy for urothelial bladder carcinoma and subsequently developed metastases (11). Our study has shown that leukocyte counts 8000/ml was a significant risk factor on multivariate analysis, while the elevation of ALP, LDH or CRP was not.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition to serum ALP reported by von der Maase et al (5), the recent report by Nakagawa et al (11) demonstrated that serum CRP and serum lactate dehydrogenase (LDH) levels were independent predictors of poorer survival, analyzing 114 patients who were treated with radical cystectomy for urothelial bladder carcinoma and subsequently developed metastases (11). Our study has shown that leukocyte counts 8000/ml was a significant risk factor on multivariate analysis, while the elevation of ALP, LDH or CRP was not.…”
Section: Discussionmentioning
confidence: 82%
“…The study also concluded that surgery should be avoided in cases with multiple liver metastases, as well as metastases involving more than one visceral site or abdominal organ, or bone metastases, especially involving the pelvis or axial skeleton (14,15). More recently, Nakagawa et al (11) showed that patients with solitary lung metastasis, long duration from radical surgery to recurrence, no neoadjuvant/adjuvant chemotherapy, no symptom and low CRP level were most likely to benefit from metastasectomy. Our study also showed that focal treatment for metastatic lesions was a statistically significant factor for better outcome.…”
mentioning
confidence: 99%
“…Early recurrence was defined as tumor recurrence within 12 months after RC. The type of recurrence was classified as local or distant disease [5,6]. The time of death was verified by local cancer registries and by the treating physician.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this aggressive treatment, subsequent disease recurrence occurs in approximately half of patients with muscle-invasive bladder cancer in the first 24 months after RC [1,3]. Over two thirds of patients with disease recurrence die within 1 year of recurrence [4,5]. Various clinicopathological parameters have been identified as predictors of overall survival (OS) in patients who experience disease recurrence after RC [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation